Milk From Cow Fed With High Forage/Concentrate Ratio Diet: Beneficial Effect on Rat Skeletal Muscle Inflammatory State and Oxidative Stress Through Modulation of Mitochondrial Functions and AMPK Activity - Trinchese, Giovanna; Cavaliere, Gina; Penna, Eduardo; De Filippo, Chiara; Cimmino, Fabiano; Catapano, Angela; Musco, Nadia; Tudisco, Raffaella; Lombardi, Pietro; Infascelli, Federico; Messina, Giovanni; Muredda, Laura; et al. (Frontiers in Physiology, 2019)
Milk and dairy products are relevant components of daily diet and are part of dietary recommendation in many countries due to their content of key nutrients. However, the relatively high content of saturated fat of the milk and its extensive usage for every age group raises concerns about its potential negative health effects. Therefore, in the last years, several researchers dedicated their attention to milk production and quality. Milk fatty acids profile depend on cow feeding and in particular on the type of forage and concentrate and forage/concentrate ratio. It was demonstrated that feeding dairy cows with a 70/30 forage/concentrate ratio yields milk with a low ω6:ω3 ratio and high CLA levels. In this work, we demonstrated that the supplementation of rats diet with this high forage milk (HFM) results, in the skeletal muscle of these animals, in a reduced lipid content and inflammation levels, and an improved mitochondrial lipid oxidation, and redox status through modulation of AMPK activity.